Post overbrengen volgens hetzelfde systeem als met de olieslang naar de Hr.MS."Evertsen" - Dussel, Wim, (1951)
Post overbrengen volgens hetzelfde systeem als met de olieslang naar de Hr.MS."Evertsen".